Cell-to-cell communication - Li, Weini (2017)
Cell-to-cell communication has become a hotspot in biological research. By means of genetic engineering, different cell components are able to exchange messages and collaborate to achieve more complicated tasks that are difficult to achieve by a single cell components. To develop the cell-to-cell communication, sender-receiver quorum sensing systems and precisely controlled gene expression, supported by communication theory, are necessary. In this project, gene sequences are expressed in different time slots with the help of regulated blue-light devices. This blue-light regulated system can synchronize the gene cells to perform various control functions, thus achieving the goals of cell-cell communications. Simulink block in MATLAB is used to develop mathematical models and guide the design of the sender-receiver system (gene circuits) with hypothetical initial gene parameter values. Then experimental results are used to estimate and optimize the gene parameters in simulation. Gene circuit like this may become a fundamental component for constructing more complex biological systems that are not previously achieved.